2017
DOI: 10.1021/acsbiomaterials.7b00757
|View full text |Cite
|
Sign up to set email alerts
|

A Polypropylene-Integrated Bilayer Composite Mesh with Bactericidal and Antiadhesive Efficiency for Hernia Operations

Abstract: Polypropylene (PP) mesh has been widely used in hernia fixation operations for more than one hundred years, and peritoneal adhesion is still one of the main complications after hernia fixation operations. For preventing peritoneal adhesion, many solutions have been offered, including gel systems, adhesion barrier membranes, and bilayer meshes. Among these, bilayer meshes come to the forefront as they serve for both hernia repair and adhesion prevention. In this study, we developed an easy and effective method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Therefore, the decoration of PP mesh surface with different biofriendly materials can provide the required biocompatibility such as enhanced cell growth 4 and microbial resistance 5 without compromising its bulk properties 6–9 . As the application of metal nanoparticles in biological areas is limited, 10 composite approach 8,11 and copolymers 12 were used to address these issues. However, the developed materials are very complex in structure, and the production techniques are cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the decoration of PP mesh surface with different biofriendly materials can provide the required biocompatibility such as enhanced cell growth 4 and microbial resistance 5 without compromising its bulk properties 6–9 . As the application of metal nanoparticles in biological areas is limited, 10 composite approach 8,11 and copolymers 12 were used to address these issues. However, the developed materials are very complex in structure, and the production techniques are cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Patches, usually used as mechanical support for tissue regeneration, are widely used in clinical practice, but currently patches are imperfect and still suffer from the potential for rejection, adhesion, etc. [ 6 ] Among these complications, postoperative adhesions may lead to serious problems, such as abdominal pain, intestinal obstruction, infertility, hernia recurrence, all of which could cause discomfort or pain as well as high costs to patients. [ 7,8 ] Therefore, many studies have focused on the fabrication of patches with good biocompatibility and sufficient mechanical properties to not only provide adequate mechanical support for tissue growth, but also to effectively avoid postoperative tissue adhesions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23–25 ] In addition, due to the limitation of process, the selected materials are usually a synthetic polymer with poor biological performance, so they often lead to pain, adhesion, and contraction with the surrounding tissues in patients in clinical practice. [ 6,26 ] Besides, the preparation process also has direct writing, pouring and so on. Although these processes can effectively prepare patches, they have shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…The main issues are the formed peritoneal adhesions combined with inflammation and a pronounced immune response of the body to a foreign material 10,11 . The newly introduced antimicrobial activity and hemostatic properties of the composite are of great importance as they enhance tissue regeneration 12–14 . It is also known the study of porous polyolefin matrices used as a membrane in artificial lungs or artificial kidneys: however, it has also been shown that to impart the required antibacterial properties and resistance to biocontamination, they need to be modified with cationic polymers 15 …”
Section: Introductionmentioning
confidence: 99%